PENGARUH KUALITAS PRODUK HALAL DAN RELIGIUSITAS TERHADAP MINAT BELI KONSUMEN PRODUK KOSMETIK WARDAH MAHASISWI IAIDA BLOKAGUNG KARANGDORO TEGALSARI BANYUWANGI - Biati, Lilit; Suprapto, Ribut; Mamlukhah, Mamlukhah; Muliana, Suci (Jurnal Ekonomi Syariah Darussalam, 2022)
The purpose of this study was to 1) Determine whether the Quality of Halal Products (X1) and Religiosity (X2) simultaneously influence Consumer Purchase Interest (Y) of Wardah cosmetic products in IAI Darussalam students; 2) Knowing whether the Quality of Halal Products (X1) and Religiosity (X2) has a partial effect on Consumer Buying Interest (Y) of Wardah cosmetic products in IAI Darussalam students. This research uses a quantitative research approach with the type of data collection through the method of distributing questionnaires or questionnaires. The sampling method in this study is a non-probability sampling method with purposive sampling technique, namely the sampling technique with certain considerations. Research Results 1) Significantly the Quality of Halal Products (X1) has an effect on Consumer Buying Interest (Y); 2) Significantly Religiosity (X2) has no effect on Buying Interest (Y); 3) Simultaneously, the strategy for the Quality of Halal Products (X1) and Religiosity (X2) has a significant effect on Consumer Purchase Interest (Y) for Wardah cosmetics products.